Canonical Wnt suppressor, Axin2, promotes colon carcinoma oncogenic activity - Wu, Zhao-Qiu (National Academy of Sciences, 2012)
Aberrant activation of canonical Wingless-type MMTV integration site family (Wnt) signaling is pathognomonic of colorectal cancers (CRC) harboring functional mutations in either adenomatous polyposis coli or β-catenin. Coincident with Wnt cascade activation, CRCs also up-regulate the expression of Wnt pathway feedback inhibitors, particularly the putative tumor suppressor, Axin2. Because Axin2 serves as a negative regulator of canonical Wnt signaling in normal cells, recent attention has focused on the utility of increasing Axin2 levels in CRCs as a means to slow tumor progression. However, rather than functioning as a tumor suppressor, we demonstrate that Axin2 acts as a potent promoter of carcinoma behavior by up-regulating the activity of the transcriptional repressor, Snail1, inducing a functional epithelial-mesenchymal transition (EMT) program and driving metastatic activity. Silencing Axin2 expression decreases Snail1 activity, reverses EMT, and inhibits CRC invasive and metastatic activities in concert with global effects on the Wnt-regulated cancer cell transcriptome. The further identification of Axin2 and nuclear Snail1 proteins at the invasive front of human CRCs supports a revised model wherein Axin2 acts as a potent tumor promoter in vivo.